1995
DOI: 10.1541/ieejias.115.402
|View full text |Cite
|
Sign up to set email alerts
|

Operating Characteristics of Switched Reluctance Motor Drivers by Square Wave Voltage.

Abstract: and Tadashi Fukao, Member (Tokyo Institute of Technology) Switched reluctance motors have been studied in twenty years but the applications have been limited to special cases. One of the main reasons of these limited applications is the complicated machine model and unclear operating characteristics of switched reluctance motors. Conventional synchronous motor models are not applicable because the current waveforms of switched reluctance motors include dc component and considerable amount of harmonics. A simpl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…In this case, and after substituting Eqs. (8) and (9), we obtain Thus, the input power P i and apparent power S can be determined using Eqs. (10) and (11).…”
Section: Rms Power and Apparent Powermentioning
confidence: 99%
See 1 more Smart Citation
“…In this case, and after substituting Eqs. (8) and (9), we obtain Thus, the input power P i and apparent power S can be determined using Eqs. (10) and (11).…”
Section: Rms Power and Apparent Powermentioning
confidence: 99%
“…In this case, by approximating the anticipated inductance variation at the motor terminals using a fundamental wave L 1 and a parameter L 0 [7][8][9], and determining values of L 1 and L 0 so that the egg-shaped diagram closely matches the actual points plotted in the P i -S plane, the model of the motor was obtained and reported in Refs. 10-12. In the process of comparing measured points with an egg-shaped diagram, similar to how it is done when using any circular diagram when the least square error is used as the estimation reference, a specific circle is selected.…”
Section: Introductionmentioning
confidence: 99%
“…In this case, by approximating the anticipated inductance variation at the motor terminals using a fundamental wave L 1 and a parameter L 0 [7][8][9], and determining values of L 1 and L 0 so that the egg-shaped diagram closely matches the actual points plotted in the P i -S plane, the model of the motor was obtained and reported in Refs. In this case, by approximating the anticipated inductance variation at the motor terminals using a fundamental wave L 1 and a parameter L 0 [7][8][9], and determining values of L 1 and L 0 so that the egg-shaped diagram closely matches the actual points plotted in the P i -S plane, the model of the motor was obtained and reported in Refs.…”
Section: Introductionmentioning
confidence: 99%
“…By measuring the input active power P i and the apparent power S by means of applying a square waveform voltage and changing its phase angle, and plotting operating points in the P i -S plane, the authors have demonstrated the near-egg shape of the resulting plot. In this case, by approximating the anticipated inductance variation at the motor terminals using a fundamental wave L 1 and a parameter L 0 [7][8][9], and determining values of L 1 and L 0 so that the egg-shaped diagram closely matches the actual points plotted in the P i -S plane, the model of the motor was obtained and reported in Refs. 10-12. In the process of comparing measured points with an egg-shaped diagram, similar to how it is done when using any circular diagram when the least square error is used as the estimation reference, a specific circle is selected.…”
Section: Introductionmentioning
confidence: 99%